(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2020)
Welding technology has an important role in the industrial world. The use of welding techniques in addition to being used for manufacturing, welding techniques are also used for the repair process. Gas Welding Metal Arc Welding (GMAW) is one of the arc welding using filler wire as a patch and protective gas that serves to protect from the oxidation process. In the GMAW welding process there are often welding defects caused by certain factors, one of which is the use of protective gases that affect the weldability in the HAZ area.This research was conducted at PT. Komatsu Remanufacturing Asia, located on Balang Island Street No. 99 RT 36, Karang Joang Subdistrict, North Balikpapan District, East Kalimantan in August 2019 to February 2020. The research method used in this study is an experiment to determine the hardness value of welded joints on low carbon steel plates with hardness brinell test in the GMAW welding process. The results of hardness testing using hardness brinell test on the use of argon shielding gas decreased the value of violence in the use of strong currents 125 A to 150 A and at strong currents 175 A has the same level of violence with the use of strong currents 150 A. While in the use of protective armix gas every strong current flow always changes in the value of violence, the greater the current is used, the level of violence will be smaller. The highest hardness value in the use of argon shielding gas is found in the use of strong currents of 125 A, namely with a brinell hardness value of 124 kg / mm2, and in the use of protective gas armix the highest brinell hardness value is 117 kg / mm2, that is, on the use of strong currents of 125 A.